Emotional and behavioral problems in children and adolescents with hearing loss and their effects on quality of life. (October 2020) - Yigider, Ayse Pelin; Yilmaz, Semra; Ulusoy, Huseyin; Kara, Tayfun; Kufeciler, Levent; Kaya, Kamil Hakan
Abstract: Purpose: Determination of mental functions in children with hearing loss is important in improving the quality of life of the child. Many scales have been developed for this purpose. In this study, it was aimed to determine the emotional and behavioral effects of both the child with hearing loss and the parent in the hearing loss and device process, and to investigate the effect of this situation on the quality of life. Methods: Forty-five children aged 7–17 years with sensorineural hearing loss with audiometric methods and 32 healthy controls without hearing problem were included in the study. All children received a Powers-Weakness Questionnaire-Self-Reporting Scale, Strengths and Difficulties Questionnaire, Child Anxiety and Depression Scale, and Kid-KINDL Quality of Life Scale. In all parents, the Parental Statement of Powers-Weaknesses Questionnaire and the Kid-KINDL Quality of Life Scale parental form questionnaires were applied. Results: In the patient group, both mother (p = 0.001) and father (p = 0.027) education levels were significantly lower than the control group. The success rate of the sick children was lower than that of healthy children (p = 0.013). According to the surveys, the quality of life scale and all subscales were significantly lower in the patient group than in the control group (p < 0.05 for each). Child depression inventory score was also significantly higher in the patient group (p = 0.005). Conclusions: Data obtained in the study indicate that children with hearing disabilities should be closely monitored and undergo a better rehabilitation process in terms of both anxiety and depression and their quality of life. According to our findings, since the parents of hearing-impaired children are observed to have a low level of education, it is seen that these families should be educated more closely in approaching children and improving their quality of life.